Pengembangan E-Commerce Berbasis Website (Studi Kasus: pada Warung Seblak Mbak Sari Desa Karangasem) - Laeli Nurul Latifah; Fersellia Fersellia (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of digital technology has driven significant transformations in the business sector, including the culinary industry, through the adoption of E-commerce. Warung Seblak Mbak Sari previously faced several challenges, such as manual transaction recording, limited market reach, and unintegrated digital promotion. This study aims to develop an E-commerce website as a solution to improve service efficiency and expand marketing reach. The method applied is Rapid Application Development (RAD), which consists of the Requirement Planning, User Design, Construction, and Cutover phases. The system was designed using Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD), and implemented using PHP and MySQL. The development results show that the website can display menus, process online orders, perform automatic checkout, manage products, and generate sales reports. Blackbox Testing proves that all features function as required, enabling the system to reduce recording errors, accelerate transaction processes, and increase marketing reach. Therefore, the implementation of this web-based E-commerce can help culinary MSMEs manage their businesses more effectively and competitively in the digital era.